2016
DOI: 10.1007/s10661-016-5562-2
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability assessment of toxic metals using the technique “acid-volatile sulfide (AVS)-simultaneously extracted metals (SEM)” in marine sediments collected in Todos os Santos Bay, Brazil

Abstract: This paper reports the bioavailability of the metals (cadmium, copper, zinc, lead, and nickel) in sediment samples collected in seven stations from the São Paulo Estuary, Todos os Santos Bay, Brazil. The bioavailability was determined by employing the technique "acid-volatile sulfide (AVS) and simultaneously extracted metal (SEM)". The elements cadmium, copper, lead, and zinc were determined using differential pulse anodic stripping voltammetry (DPASV), while nickel was quantified utilizing electrothermal atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Previous studies have shown high concentrations of pollutants in this area, including hydrocarbons (Queiroz and Celino, 2008a, b;Silva et al, 2014) and trace elements, mostly copper (Hatje and Barros, 2012;Andrade et al, 2017). Despite pollution having been reported in the BTS (Milazzo et al, 2014;Rocha et al, 2016;Andrade et al, 2017), most of the studies carried out focused on total levels in soil and sediments, with works on bioavailability based mainly on the quantification of acid-volatile sulphides and metals extracted simultaneously (AVS-Me; Silva-Júnior et al, 2016;Brito et al, 2020). This technique has limitations with regard to the quantification of sulfides, with underestimation of concentrations in the system as well as of metallic bioavailability (Cooper and Morse, 1998;Luther, 2005), since it disregards other associations established between metals and other geochemical phases of soils/sediments (Huerta-Días and Morse, 1992;Otero and Macías, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown high concentrations of pollutants in this area, including hydrocarbons (Queiroz and Celino, 2008a, b;Silva et al, 2014) and trace elements, mostly copper (Hatje and Barros, 2012;Andrade et al, 2017). Despite pollution having been reported in the BTS (Milazzo et al, 2014;Rocha et al, 2016;Andrade et al, 2017), most of the studies carried out focused on total levels in soil and sediments, with works on bioavailability based mainly on the quantification of acid-volatile sulphides and metals extracted simultaneously (AVS-Me; Silva-Júnior et al, 2016;Brito et al, 2020). This technique has limitations with regard to the quantification of sulfides, with underestimation of concentrations in the system as well as of metallic bioavailability (Cooper and Morse, 1998;Luther, 2005), since it disregards other associations established between metals and other geochemical phases of soils/sediments (Huerta-Días and Morse, 1992;Otero and Macías, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals have been increasing in the global environment since the industrial evolution [1]. Metals in aquatic natural systems are of concern to regulators because they can be toxic at concentrations above ambient conditions, non-biodegradable in the environment, and accumulate in animal and plant tissue [2]. Many metals are essential for living organisms, yet can be toxic at high concentrations [3].…”
Section: Introductionmentioning
confidence: 99%
“…In aquatic ecosystems, sediments are the main sink for metals [4]. Sources for metals in the environment are both anthropogenic and natural and include effluents from wastewater treatment plants, industrial and agricultural wastes, power stations, mining, boating activities, transportation vehicles, urban runoff, and geological processes [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is one study where a brief review of SEM copper data based on just agricultural use has been conducted [9]. Anthropogenic sources for SEM copper in the aquatic environment include wastewater treatment plants, various industrial wastes, stormwater runoff, mining activities, antifouling boat paints, and agricultural use [10][11][12]. For example, copper-based compounds are used as fungicides to protect crops from important diseases in many areas of the world.…”
Section: Introductionmentioning
confidence: 99%